2016
DOI: 10.1152/jn.00465.2015
|View full text |Cite
|
Sign up to set email alerts
|

Selection of head and whisker coordination strategies during goal-oriented active touch

Abstract: In the rodent whisker system, a key model for neural processing and behavioral choices during active sensing, whisker motion is increasingly recognized as only part of a broader motor repertoire employed by rodents during active touch. In particular, recent studies suggest whisker and head motions are tightly coordinated. However, conditions governing the selection and temporal organization of such coordinated sensing strategies remain poorly understood. We videographically reconstructed head and whisker motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…EMG wires run anterior to the eyes, where they meet the scalp resection and are adhered to the skull with dental cement (figure 1(a)). Mice had been trained to locate a randomly positioned reward-port in the dark using whisker palpations [28]. We sought to deliver optical stimulation to primary somatosensory cortex (SI) that was timed to the whisker motions of the animal using the EMG signal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EMG wires run anterior to the eyes, where they meet the scalp resection and are adhered to the skull with dental cement (figure 1(a)). Mice had been trained to locate a randomly positioned reward-port in the dark using whisker palpations [28]. We sought to deliver optical stimulation to primary somatosensory cortex (SI) that was timed to the whisker motions of the animal using the EMG signal.…”
Section: Resultsmentioning
confidence: 99%
“…anesthetized preps, head fixation, and whisker trimming in the rodent whisker system). The importance of experiments that allow for more natural behaviors is also becoming clear [28]. By incorporating the ability to easily perform closed-loop stimulation experiments within a drive that has been engineered to accommodate more natural behaviors (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work has shown that whisker asymmetry arises and is related to movement of the head (Towal and Hartmann, 2006;Grant et al, 2009;Schroeder and Ritt 2016). These earlier studies were all in freely moving animals.…”
Section: Whisker Asymmetry In Freely Moving Animalsmentioning
confidence: 99%
“…While it is often called a model sensory system (Van der loos and Woolsey, 1973), where each whisker is associated with 1000s of neurons in the trigeminal somatosensory pathways, this system is in fact also a model motor system -with single muscles associated with each whisker (Dorfl, 1983;Sachdev et al, 2002;Grinevich et al, 2005;Haidarliu et al 2013). Not only do mice have the potential to control the motion of these tactile sensors individually, but the motion of the whiskers is often coordinated with motion of the head (Towal and Hartmann 2006;Schroeder and Ritt, 2016). Additionally, whisking can be triggered by sniffing, chewing, licking and walking (Welker 1964;Deschenes et al, 2012;Sofroniew et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Mice and rats are competent climbers and possess good grasping skills (Schmidt and Fischer 2010) that are thought to be guided by a combination of olfactory, visual and tactile cues (Bhattacharyya and Bhalla 2015;Niederschuh et al 2015;Schroeder and Ritt 2016). However, the tactile whisker sense plays a primary role in environmental exploration and locomotion in both rats and mice (Vincent 1912;Watson 1907).…”
Section: Introductionmentioning
confidence: 99%